2019
DOI: 10.3389/fpubh.2019.00164
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Delineation of Zoonotic Origins of Clostridium difficile

Abstract: Clostridium difficile is toxin-producing antimicrobial resistant (AMR) enteropathogen historically associated with diarrhea and pseudomembranous colitis in hospitalized patients. In recent years, there have been dramatic increases in the incidence and severity of C. difficile infection (CDI), and associated morbidity and mortality, in both healthcare and community settings. C. difficile is an ancient and diverse species that displays a sympatric lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 200 publications
2
72
0
Order By: Relevance
“…S7). At least some of this enormous diversity may be due to the occupation of multiple, distinct ecological niches, as exemplified by differential propensities for colonizing non-human host species () [43, 44]. Individual CCs may also differ in their aptitudes for epidemic spread, as indicated by drastically different proportions of genomes assigned to HC2 chains: only 7% of CC141 were assigned to HC2 clusters versus 35% of CC34 and 77% of CC4 ().…”
Section: Discussionmentioning
confidence: 99%
“…S7). At least some of this enormous diversity may be due to the occupation of multiple, distinct ecological niches, as exemplified by differential propensities for colonizing non-human host species () [43, 44]. Individual CCs may also differ in their aptitudes for epidemic spread, as indicated by drastically different proportions of genomes assigned to HC2 chains: only 7% of CC141 were assigned to HC2 clusters versus 35% of CC34 and 77% of CC4 ().…”
Section: Discussionmentioning
confidence: 99%
“…One possible source of C. difficile acquisition in the community is exposure to composted products during gardening and/or farming as composted products frequently contain animal manure (USDA Organic Composting Guidelines, 2017) and dewatered human biosolids from wastewater treatment plants (Xu et al ., 2016). With the widespread use of antimicrobials in large‐scale animal farms, production animals have become amplification hosts for C. difficile (Knight and Riley, 2019). Several studies have also demonstrated a high prevalence of C. difficile in raw and treated wastewater (Romano et al ., 2012; Xu et al ., 2014), human biosolids (Xu et al ., 2014) and in rivers that received the treated wastewater (Xu et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Toxinotypes are therefore important from clinical, diagnostic, research and development perspectives. However, so far, only a few toxinotype representatives have been included in comparative genomic studies, performed either for epidemiological purposes [14][15][16][17] or for understanding virulence [18][19][20]. In addition, the evolution of the PaLoc was previously investigated with respect to the known population structure of the species, but in these reports not all known PaLoc variants, as defined by toxinotype, were included [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%